HUBUNGAN INTENSITAS PENGGUNAAN MEDIA SOSIAL DENGAN KRISIS SEPEREMPAT KEHIDUPAN PADA RELAWAN ORGANISASI X TAHUN 2021 - Indah Sukmawati (2021)
These days there is a new phenomenon frequently discussed namely Quarter-Life Crisis. This phenomena include the feeling of hesitant, anxious, sad, broken-hearted, contrary self-evaluation, concerns about interpersonal connections, to feeling caged in awful situations. Currently, social media users continue to expand which directly affects the manner of living, specifically mental health. The objective of this study was to decide the connection between respondent characteristics and their social media use with quarter-life crisis. This quantitative research with cross-sectional method using chi-square test. The volunteers of Organization X are the population in this study with a total sampling technique, and 45 respondents were found. The research was conducted in Organization X on December 2021 using a questionnaire. As result, it was found that age, gender, and type of social media had a p-value > 0.05 and educational background, occupation, income, and intensity of use of social media had a p-value < 0.05. As conclusion, age, gender, and type of social media are not related to quarter-life crisis. While the educational background, work, income and intensity of social media use are related to quarter-life crisis. The suggestion from this study is to increase public awareness, especially those entering adulthood, about mental health awareness.